Gaya Bahasa Kumpulan Puisi Frasa di Penghujung Musim Karya Adiska Nirmaya dan Kumpulan Puisi Nafas Karya Fatima Musawa Melalui Pendekatan Perbandingan Sastra - Agung Nugroho; Inda Puspita Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to gain an understanding of the comparison of language styles in a collection of End-of-Season Phrases by Adiska Nirmaya and a collection of Nafaskarya Fatimah Musawa poems. The method used is qualitative descriptive. Data collection techniques in research using documentation techniques. Data analysis techniques with steps: data reduction, data display, and conclusion and verification. The results of the study show that there are comparisons of comparative language styles and opposing language styles. Comparative language style in the collection of End-of-Season Phrases by Adiska Nirmala amounts to 18 data and the language style of contention is 5 data, based on the language style that dominates the collection of Phrase Poems at the End of Season. Whereas the collection of Nafas poems by Fatimah Musawa, namely: Language style comparisons totaling 9 data. While the language style of contention is 11 data. Conclusions, a collection of End-of-Season Phrases by Adiska Nirmaya is more dominant in the style of comparison and the collection of Nafas poems by Fatima Musawa has a dominant style of language in opposition. Keywords: Language Style, Collection of Poetry.